THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE AND HIV/AIDS PREVENTION BEHAVIOR IN THE WORKING AREA OF PUTRI AYU PUBLIC HEALTH CENTER - Sari, Winna Kurnia; Mulyati, Sri; Suryani, Dini; Sinaga, Maria Hotmauli (STIKES Syedza Saintika Padang, 2025)
The Human Immunodeficiency Virus (HIV) issue has become a major one threatening Indonesia and many countries globally. The number of People Living with HIV receiving Antiretroviral (ARV) therapy in Jambi province is 1015 people. The Men who have Sex with Men (MSM) group is at high risk of contracting HIV due to risky sexual behavior, and the level of knowledge is a crucial factor in prevention. This study aims to determine the relationship between knowledge and HIV/AIDS prevention behavior within the MSM group. The research is a quantitative study with a cross-sectional design. The population consisted of 110 people, and the sample for this study was 52 individuals, taken through purposive sampling. The study was conducted from August 7 to August 27, 2025. The data analysis used was Univariate and Bivariate Analysis utilizing the chi-square test. The results show that the majority of respondents have sufficient knowledge regarding HIV/AIDS prevention, totaling 32 people (61.5%), and the majority of respondents have good HIV/AIDS prevention behavior, totaling 29 people (55.8%). It is recommended that the Community Health Center (Puskesmas) continues to enhance and support the HIV/AIDS program by conducting socialization efforts on HIV/AIDS prevention through education, counseling, and guidance focused on MSM.Keywords: Knowledge; Prevention Behavior; HIV/AIDS; Men who have Sex with Men